2021
DOI: 10.1186/s12879-021-06029-3
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection and bacterial microbiota in the semen from healthy men

Abstract: Background Aberrant microbiota composition has been linked to disease development at numerous anatomical sites. Microbiota changes in reaction to viral infections, such as human papillomavirus (HPV), have been investigated almost exclusively in the female reproductive tract. However, HPV infection may also affect male health by reducing semen quality and fertility. The aim of this study was to investigate whether present HPV DNA is associated with detectable changes in semen bacterial microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Tuominen et al . 31 found 19% HPV in their semen samples, and only one-third of the HPV-positive patients had high oncologic risk subtypes.…”
Section: Discussionmentioning
confidence: 97%
“…Tuominen et al . 31 found 19% HPV in their semen samples, and only one-third of the HPV-positive patients had high oncologic risk subtypes.…”
Section: Discussionmentioning
confidence: 97%
“…HPV was the first virus included in this panel, as it is usually present in semen samples [ 34 , 129 , 195 , 196 ]. Furthermore, according to Boeri et al [ 197 ], accurate investigation of the presence of seminal HPV in the diagnostic analysis of infertile men is of paramount importance, not only for its potential negative pathophysiological impact on male fertility but also in terms of the general health of men.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to CYP2E1 expression, the results demonstrate that the highest signal found in this study by HPV infection was the overexpression of CYP2E1, and moreover, a differentially higher expression was detected in MI-HPV compared to SI-HPV. Concerning this finding, a recent study showed that men with seminal HPV DNA had higher relative abundance of specific seminal bacteria compared to men without seminal HPV DNA [ 36 ]. In this study, the overexpression of CYP2E1 could be caused by metabolites generated by co-infection with other microbes, as has been described in previous studies [ 5 , 6 , 25 ], and the higher overexpression in MI over SI could be explained by the higher abundance of HPV diversity and a higher abundance of resident microbes.…”
Section: Discussionmentioning
confidence: 99%